(untitled) (Хабаршы. Психология және социология сериясы, 2019)
This scientific article on the topic “The problem of occupational stress as one of the factors of the deterioration of the psycho-emotional state of medical workers” aimed at studying the problem of the influence of occupational stress on the psycho-emotional state, working capacity and performance of medical workers. The following types of occupational stress were identified in the process of studying: work stress, occupational stress and organizational stress as well as the causes that give rise to above mentioned stresses and stress types. In addition, we looked at the following phases of development of occupational stress: the phase of tension, the phase of resistance and the phase of exhaustion, which manifest themselves in the following signs: 1. The phase of tension. Acute experiences, dissatisfaction with themselves and anxiety prevail. 2. The phase of resistance. There is a decrease in emotional response level; attempts to reduce the list of functional responsibilities. The doctor becomes less emotional within the family and while communicating with friends. 3. The phase of exhaustion. Lack of emotions, harshness, rudeness, lack of sympathy, touchiness, detachment, psychosomatic and vegetative disorders. Finally, conclusions about the causality and symptomatology of the deterioration of the psychoemotional state of medical workers were drawn, questions about recommendations that contribute to the prevention of the stress state associated with professional activities and issues about the recommendations and prevention of stressful conditions associated with professional activities were examined.